1982
DOI: 10.1111/j.1440-169x.1982.00531.x
|View full text |Cite
|
Sign up to set email alerts
|

Fine Structural Changes in the Acrosome Reaction of the Japanese Abalone, Haliotis disus. (abalone/sperm/acrosome reaction/ultrastructure)

Abstract: The spermatozoon of the Japanese abalone, Haliotis discus, and its structural changes during the acrosome reaction were observed by electron microscopy. The spermatozoon has a huge acrosome in the shape of a hanging bell or a forefinger with a deep fossa at the posterior end being filled with a bundle of microfilaments. The membranes of the acrosomal apex, the so-called trigger region, are structurally discernible from those of other acrosomal regions. Following the trigger region, a unique structure under the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
21
0

Year Published

1984
1984
2001
2001

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 10 publications
8
21
0
Order By: Relevance
“…The previous study (12) concerning the acrosome in H. discus shows that the mode of its reaction is fundamentally similar to those of the species mentioned above, except that a novel structure termed the "truncated cone" is observed at the apical part of the acrosomal vesicle. Such a peculiar structure has not been found in other species so far, and this may indicate that this structure plays a role in fertilization unique for Haliotis.…”
supporting
confidence: 56%
See 2 more Smart Citations
“…The previous study (12) concerning the acrosome in H. discus shows that the mode of its reaction is fundamentally similar to those of the species mentioned above, except that a novel structure termed the "truncated cone" is observed at the apical part of the acrosomal vesicle. Such a peculiar structure has not been found in other species so far, and this may indicate that this structure plays a role in fertilization unique for Haliotis.…”
supporting
confidence: 56%
“…At the apex of the acrosome of H. discus spermatozoon, the truncated cone is found underneath the acrosomal membrane, as if it covers the apical surface of the acrosomal contents except for the trigger region (12). In a longitudinal section, the truncated cone is observed as two bars, being about 0.3 pm long by 20 nm wide, at both sides of the trigger region (Fig.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…In the unreacted abalone sperm, filipin-induced deformation was seldom observed on the inner acrosomal membrane, which was densely packed with IMPs (29). Considering that this membrane tightly surrounds a bundle of actin filaments in the shaft region (36) and is undercoated with an electron-dense layer in the funnel-shaped region (28), our present result is in aggreement with those studies performed on other membrane systems, such as coated pits, desmosomes, tight junctions and intermediate junctions. These studies have reported that membrane domains with IMP aggregations or filamentous underlying usually lack filipin-sterol complexes (7,14,20,26,32).…”
Section: Discussionsupporting
confidence: 86%
“…It has been noted in certain membrane areas that membrane-associated proteins interfere with the formation of filipin-sterol complexes (8). In the present result, the sparsely distributed filipin-labelled area closely corresponds to the region where the outer acrosomal membrane is undercoated with an electron-dense material, as seen in the thin sections (28). Such sparse distribution of filipin labelling in the outer acrosomal membrane, therefore, could be caused by the interference of this electron-dense material with the filipin-sterol reaction by masking or linking the free sterols.…”
Section: Discussionsupporting
confidence: 76%